Ripening season, ethylene production and respiration rate are related to fruit non-destructively-analyzed volatiles measured by an electronic nose in 57 peach (Prunus persica L.) samples - Su, Mingshen; Ye, Zhengwen; Zhang, Bo; Chen, Kunsong (Emirates Journal of Food and Agriculture, 2017)
Fifty-seven peach samples from 19 peach cultivars were gathered at consumption maturities from an orchard between July 21 and September 9 in 2010. Fruit ethylene production (C2H4) was significantly positively correlated with respiration rate (CO2) for tested samples. Fruit non-desctructively-analized volatiles were measured by a FOX 4000 electronic nose (e-nose), which 57 samples were classified into three groups according to ripening season, respiration rate and ethylene production to evaluate the volatile separations. Samples harvested in July, August and September in 2010, samples of high (>25) respiration rate (mL.Kg-1FW.h-1 CO2) and low ones (<16), samples of high (>10) ethylene production (nL.g-1 FW.h-1 C2H4) and low ones (<2) ones could be clearly separated in the discriminant factor analysis (DFA) plots based on fruit volatiles of the e-nose measurements. Intensity values of T30/1, T70/2, PA/2, P30/1, P40/2, P30/2 and T40/2 sensors of the e-nose measurements were in accord with the classifications of harvest seasons, respiration rate and ethylene production. Non-desctructively-analized volatiles, respiration rate and ethylene production were somewhat related each other despite genotype and environmental factor in the tested peach fruit samples.